Continuous BIM-based assessment of embodied environmental impacts throughout the design process. (20th February 2019) - Cavalliere, Carmine; Habert, Guillaume; Dell'Osso, Guido Raffaele; Hollberg, Alexander
Abstract: Life Cycle Assessment (LCA) is a suitable method to analyse and improve the environmental impact of buildings. However, it is complex to apply in the design phase. Building Information Modelling (BIM) can help to perform LCA during the design process. Current BIM-LCA approaches follow two trends. Either they use complex models in detailed design phases, when it is late for major changes, or they are based on simplified approaches only applicable in early design stages. This paper proposes a novel method for applying LCA continuously over the entire building design process to assess the embodied environmental impacts by using the data provided by BIM with as much accuracy as possible in each stage. The method uses different LCA databases with different levels of detail for the specific level of development (LOD) of the BIM. Since different building elements are not modelled with identical LODs in each design phase, the assessment of embodied environmental impacts is conducted by consistently mixing the LCA databases, which is possible as long as the databases use identical background data. The method is applied to five design stages of a building case study. The results show that it is now possible to calculate the embodied impacts in all design stages while being consistent with the results from the completed project. The environmental impact in a certain design phase is always within the range of variability of the previous phase. Therefore, the method allows to estimate the final embodied environmental impact with increasing accuracy and by that provide information for decision-making throughout the whole design process.